Impact of smoking on protein levels of beta-defensins in periodontal disease - Soldati, Kahena Rodrigues [UNESP]; Gutierrez, Lorena Silva [UNESP]; Anovazzi, Giovana [UNESP]; Scarel-Caminaga, Raquel Mantuaneli [UNESP]; Zandim-Barcelos, Daniela Leal [UNESP] (FapUNIFESP (SciELO), 2022)
Antimicrobial peptides (AMPs) are important components of the host response against invading pathogens. In addition to their direct antimicrobial activity, they can also participate in the immune system modulation. However, the role of AMPs in the etiopathogenesis of periodontal disease and the risk factors that may influence their expression in the oral cavity are not fully understood. The aim of this study was to determine the impact of smoking on beta-defensin (hBD) 1 and 2 levels analyzing samples from periodontitis patients. Fifty patients with periodontitis, 25 smokers and 25 non-smokers, and 20 periodontally healthy patients were recruited. After periodontal clinical evaluation, gingival crevicular fluid (GCF) samples were collected from healthy sites of patients without periodontal disease and from healthy and diseased sites of patients with periodontitis. Peptides quantification was performed by sandwich ELISA technique. Smokers showed reduced GCF hBD 1 levels and increased hBD 2 levels compared to non-smokers in diseased sites (p <0.05). Higher levels of hBD 1 were observed in healthy sites of patients without periodontal disease than in healthy sites of patients with periodontitis (p<0.0001). Diseased sites of non-smokers presented higher levels of hBD 2 than healthy sites (p <0.05). These results reveal that protein levels of hBDs 1 and 2 can be impaired by cigarette smoking in the presence of periodontal disease.